The development of a flow-through dissolution method for injectable silica-based drug delivery formulations for subcutaneous administrations - Järvensivu, Päivi (My University, 2023)
Silica (silicon dioxide) is used as a biomaterial in various medical applications, e.g., in dentistry, orthopedics, and medical devices. There has been increasing interest of developing silica-based products especially for parenteral formulations to improve drug dosing. The encapsulated drug from biodegradable silica-based products is released in a controlled manner over a period of time, which can range from days to years. The advantage of long-term parenteral administration is that it reduces fluctuations in drug concentration in the body and reduces the frequency of administration. DelSiTech Ltd. has developed an injectable, silica-based drug delivery technology in which the drug is encapsulated in silica microparticles and released in a controlled manner. In vitro dissolution test is an important analytical method used to study the release rate of drug from different drug formulations. In particular, the in vitro flow-through dissolution method is considered the best method to mimic the in vivo environment of subcutaneous or intramuscular parenteral formulations. The aim of this study was to develop a flow-through dissolution method which is able to mimic in vivo release of injectable silica-based drug formulations when dosed subcutaneously. The flow-through dissolution system was optimized to achieve conditions mimicking the subcutaneous environment. In the developed flow-through system, fresh physiological buffer continuously passes through the flow cell containing the silica-based drug product (depot). The concentration of drug and silica was analysed at different time points from the flow through system and compared to the sample and separate method in sink condition which is currently used as the dissolution method at DelSiTech. Previous studies have shown that subcutaneously injected silica hydrogel depots dissolve ten times slower in vivo than with the sample and separate method. For this reason, the aim of optimization was to have the dissolution rate in the flow-through system ten times slower than with the sample and separate method, thus the flow-through dissolution system would mimic the dissolution rate in vivo. Ultimately, the target dissolution rate with ten times slower dissolution rate of silica was achieved by using a flow rate of 22 µl/min in the studied formulation. The dissolution studies with the flow-through system showed that the dissolution results were inconsistent when compared the flow-through dissolution with the sample and separate method with different formulations. However, the flow-through system was able to distinguish between crushed and non-crushed silica-based depots. The dissolution rate of silica with crushed depot was clearly increased compared to the non-crushed depot. These results obviously show that the shape of the depot and the reactive outer surface area have an importance on dissolution rate of silica and consequently on the release of drugs. To obtain more consistent results, the flow-through system would need to be further optimized and tested with different formulations to verify and validate the system for subcutaneously injectable depots.

Silikaa eli piidioksidia käytetään biomateriaalina useissa eri lääketieteen sovelluksissa, kuten hammaslääketieteessä, ortopediassa, sekä lääkinnällisissä laitteissa. Lääkeaineiden annostelun parantamiseksi on erityisesti kehitetty biohajoavaan silikaan pohjautuvia parenteraaliseen annosteluun tarkoitettuja lääkevalmisteita. Biohajoavista silikapohjaisista lääkeannosteluvalmisteista lääkeaine vapautuu kontrolloidusti halutun ajanjakson, joka voi olla päivistä, jopa vuosiin. Pitkäaikainen parenteraalinen lääkeannostelu vähentää elimistön lääkepitoisuuden vaihtelua, sekä annostelutiheyttä. Pitkäaikaiseen ihonalaiseen annosteluun on DelSiTech Oy kehittänyt injektoitavan silikageelivalmisteen, jossa lääkeaine on kapseloitu silikamikropartikkeleihin, joista lääkeaine vapautuu kontrolloidusti. Lääkeaineen in vitro dissoluutiokokeet eli vapautumiskokeet ovat tärkeitä analyysimenetelmiä lääkeaineen vapautumisnopeuden selvittämiseksi lääkevalmisteista. Erityisesti in vitro menetelmistä läpivirtausmenetelmää pidetään parhaana menetelmänä jäljittelemään in vivo olosuhteita. Työn tavoitteena oli kehittää läpivirtausdissoluutiomenetelmä ihon alle injektoitaville silikageelivalmisteille. Kehitetyn läpivirtausdissoluutiolaitteiston olosuhteet pyrittiin optimoimaan muistuttamaan ihon alaisia olosuhteita. Kehitetyssä läpivirtausdissoluutiolaitteistossa fysiologista puskuria pumpataan 37-asteisessa vesihauteessa olevaan astiaan, joka sisältää silikapohjaisen lääkevalmisteen. Läpimenneestä puskurista määritettiin silikan ja lääkeaineen pitoisuudet useissa aikapisteissä, joita verrattiin käytössä olevaan näytteenotto- ja erotus -dissoluutiomenetelmään. Aikaisemmat tutkimukset ovat osoittaneet, että injektoivat silikahydrogeelivalmisteet liukenevat kymmenen kertaa hitaampaa in vivo kuin in vitro näytteenotto- ja erotusmenetelmällä. Sen vuoksi optimoinnin tavoitteena oli kymmenen kertaa hitaampi silikan vapautuminen verrattuna näytteenotto- ja erotusmenetelmään, jolloin läpivirtausmenetelmä jäljittelisi in vivo dissoluutionopeutta. Tavoiteltu silikan dissoluutionopeus saavutettiin käyttämällä 22 µl/min virtausnopeutta. Läpivirtausmenetelmällä saadut vapautumiskokeiden tulokset olivat epäjohdonmukaisia eri formulaatioilla verrattuna näytteenotto- ja erotusmenetelmään. Läpivirtausmenetelmä pystyi kuitenkin erottamaan rikotun hydrogeelivalmisteen ja ehjästä valmisteesta. Rikotun hydrogeelivalmisteen silikan vapautumisnopeus oli selvästi nopeampi kuin ehjän valmisteen. Nämä tulokset osoittavat, että silikageelivalmisteen muoto ja reaktiopinta-ala vaikuttavat silikan liukenemiseen ja siten lääkkeen vapautumisnopeuteen. Kehitetty läpivirtausmenetelmä vaatisi lisää testausta ja optimointia eri formulaatioilla, jotta voitaisiin saada johdonmukaisempia tuloksia ja varmentaa menetelmän toimivuus injektoitaville silikavalmisteille.
Keywords: flow-through dissolution, parenteral administration, silica-based drug delivery